Presença de sulfito de sódio e sua influência nas características físico-químicas e microbiológicas de carnes bovinas moídas resfriadas - Daniele Hübner Bonfada (Acta Scientiae Veterinariae, 2012)
Background: Ground meat stands among the most consumed meat products, being its safety easily damaged by increasing the surface area of contact after grinding it, what facilitates the growth of pathogenic and deteriorating micro-organisms. In order to decrease the lost because of deterioration, trade has been utilizing fraudulent devices as the addition of intentional preservative such as sodium sulfite. This research aimed to identify the presence of sodium sulfite in cooled ground beef commercialized in business establishments located in Porto Alegre city, state of Rio Grande do Sul, Brazil. In addition, it addressed the evaluation of the influence of using this addictive in cooled ground meat front its physic-chemical and microbiological characteristics and residual capacity in the first 48 hours.